Interview with Professor William O´Reilly (University of Cambridge, Trinity Hall) - Čapská, Veronika (Dějiny – teorie – kritika, 2018)
On the occasion of the invited visit of Dr William O’Reilly (University of Cambridge, Trinity Hall) to Prague and his lecture entitled Selling Souls organized jointly by the Charles University in Prague and Centre français de recherche en sciences sociales, an interview with Dr O’Reilly took place in Café U Rotlevů in Prague on November 7th 2017. The interview focuses on and honours his long-term research. With this the journal History – Theory – Criticism/ Dějiny – teorie – kritika aims raise awareness of his work in which early modern Central and Eastern Europe occupies an important place.